2019
DOI: 10.1007/s11104-019-04338-w
|View full text |Cite
|
Sign up to set email alerts
|

Legumes increase grassland productivity with no effect on nitrous oxide emissions

Abstract: Aims Grasslands are important agricultural production systems, where ecosystem functioning is affected by land management practices. Grass-legume mixtures are commonly cultivated to increase grassland productivity while reducing the need for nitrogen (N) fertiliser. However, little is known about the effect of this increase in productivity on greenhouse gas (GHG) emissions in grass-legume mixtures. The aim of this study was to investigate interactions between the proportion of legumes in grass-legume mixtures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 71 publications
3
28
0
Order By: Relevance
“…However, in a recent field experiment at Site G5 (Fuchs et al, 2018), N 2 O‐Int was reduced from 0.42 g N kg DM −1 yr −1 on a fertilized control obtaining fertilizer N via slurry (240 kg N, 4–15% clover) to 0.28 g N kg DM −1 yr −1 at the clover treatment (23–40% clover and no N fert ) over a 2‐year observation period. Further, lab experiments by Barneze et al (2019) confirmed the model results that higher clover proportions increase productivity without affecting N 2 O emissions, resulting in reduced N 2 O‐Int.…”
Section: Discussionmentioning
confidence: 64%
“…However, in a recent field experiment at Site G5 (Fuchs et al, 2018), N 2 O‐Int was reduced from 0.42 g N kg DM −1 yr −1 on a fertilized control obtaining fertilizer N via slurry (240 kg N, 4–15% clover) to 0.28 g N kg DM −1 yr −1 at the clover treatment (23–40% clover and no N fert ) over a 2‐year observation period. Further, lab experiments by Barneze et al (2019) confirmed the model results that higher clover proportions increase productivity without affecting N 2 O emissions, resulting in reduced N 2 O‐Int.…”
Section: Discussionmentioning
confidence: 64%
“…Similarly, Niklaus et al [59] reported a significant legume effect on N 2 O emission. On the contrary, Barneze et al [65] found no legume effect on N 2 O emission, total mineral N or mineral N in fertilized or unfertilized soils.…”
Section: Factors That Controlled N 2 O Emission and Ef At The Site 4mentioning
confidence: 92%
“…Under monoculture, legumes appeared to emit more N 2 O than other species [59]. However, this might not be necessarily additive in mixed pastures [66], but increases in the proportion of legumes might influence C and N cycling processes [65]. This legume effect on N 2 O emission might be related to the increased N supply (Table 3), leading to nitrification and denitrification losses.…”
Section: Factors That Controlled N 2 O Emission and Ef At The Site 4mentioning
confidence: 99%
See 1 more Smart Citation
“…Trials in the UK have shown that grass plus red clover swards utilise available nutrients more efficiently than grass monocultures, contributing to increased yield of subsequently planted cereals (Doel 2013). Grass plus red clover swards have also been found to increase production of above ground biomass, dry matter yield, and digestible organic matter compared to grass monocultures (de Haas et al 2019;Barneze et al 2020). However, despite improving dry matter yield when grown in a grass mixture compared with grass monocultures (de Haas et al 2019;Barneze et al 2020), red clover is not as well suited to grazing as white clover due to lower production potential in grazed swards and is, therefore, grown more for silage for winter feeding of ruminants (Frankow-Lindberg 2017).…”
Section: Agronomic Benefits Of Grass Plus Clover Swardsmentioning
confidence: 99%